The Strategy Development of Naval Technology to Support the Principal Task of Navy Operations - Ahmadi, Didit Herdiawan, Amarulla Octavian (International Journal of Advanced Science and Technology, 2020)
development strategy has an important role to encounter naval defense and security threat. This research aimed at formulating a strategy to develop naval technology to strengthen the integrated naval weapon system.This research used SWOT (Strength, Weakness, Opportunity, Threat) analysis method as strategy formulation. Secondly, this research used the Interpretative Structural Modeling (ISM) and Balanced Scorecard approach. Naval technology development strategy in the integrated fleet weapon system (SSAT) which was based on naval technology was formulated into a strategic management plan which was based on five points of SO strategy, three points of ST strategy, six points of WO strategy and one point of WT strategy that made in fifteen stages of strategy in the naval technological mastery. The strategy mapping created in the Balanced Scorecard structure presented that financial perspective was made of one strategy target. Nine strategy targets were in the internal process perspective. Learning & Growth perspective was made of four strategy goals. In addition, customer aspect consisted of one strategy goal. This research was expected to give contribution to the naval strategic development to support the integrated fleet weapon system in the Indonesian Navy. Keyword : Naval Technology, Integrated Fleet Weapon System, SWOT Analysis, Interpretative Structural Modeling (ISM), Balanced Scorecard (BSC).